EVALUASI PELAYANAN PRIMA DALAM PERPAJAKAN (STUDI PADA KANTOR PELAYANAN PAJAK PRATAMA MALANG UTARA DAN MALANG SELATAN) - Hary, Nur Esa Febrica (Jurnal Mahasiswa Perpajakan, 2014)
Excellent serviceisone of the goalsofmodernizationinDirektorat Jenderal Pajak environment. In order togivethe best servicefromthe taxpayeris expected tobe amotivationforeachtax office tofixthe service. Excellent service isthe best servicein accordancewith the standardsheld byeach organization. Pratamatax service officeas aspearheadinthe taxserviceshouldpay attention tomattersrelating toexcellent service such as ability, attitude, appearance, attention, actionandresponsibility. The purposeofthis reasearchis to describe howthe service providedby the pratama tax service officeandevaluate theimplementation ofexcellent servicepratamatax servicesoffice.this study aims to describe and evaluate the excellent service in taxation based on each office in Pratama Tax Service Office of North Malang and Pratama Tax Service Office of South Malang. The method for this study is descriptive research with quantitative approach using a questionnaire survey to taxpayers that registerd in each tax office. The results showed, each pratama tax officehasexcellent serviceindicatorscriteria thatused in this reaserch. Responsibility indicatoristhe highest averagevalue ofwhich is4.440; 4.240; 4.270foreachitem. The lowest averagevalue oftheindicatoris Attentionin the third question item, the score is 3.680. Tosimplify monitoring the implementation ofexcellent serviceeachtax services officeservicespratamacreatea road map, toidentifygapsthatmakeeach oftheseofficeshave not yet reachedthewholeexcellent servicethenintervene them andfix it Keywords:Excellent Service, Pratama Tax Service Office, Evaluate